Comparison of triple frequency GNSS carrier phase and pseudorange noise using various satellite constellations - Roberts, Gethin Wyn; Hancock, Craig M.; Tang, X. (2018)
The first Global Positioning System (GPS) satellite was launched in 1978, and today there are 4 Global Navigation Satellite Systems (GNSS), with a further 7 Space Based Augmentation Systems (SBAS) and Regional Navigation Satellite Systems (RNSS) transmitting data. Further to this, these systems consist of three basic types of satellite orbits, namely Mid Earth Orbiting (MEO), Geosynchronous Orbits (GEO) and Inclined Geosynchronous Orbits (IGSO) operating at different altitudes. It is now possible to see and take measurements up to almost 50 satellites at any instant in some parts of the world, and typically in the region of 30 in most parts of the world. Originally, GPS transmitted data on two carrier frequencies, namely L1 and L2. Today’s GPS satellites transmit a variety of contemporary and original code data on three carrier frequencies; L1, L2 and L5. Similarly, other GNSS transmit on three or more carrier frequencies. This paper looks at the quality of the data from GPS, BeiDou, Galileo, GLONASS and QZSS, looking at the different satellite constellations used, as well as the different frequencies and also the historical satellite systems such as the various GPS blocks. The approaches used in this paper, are those also used for cycle slip detection. These are namely the range residual (code-carrier), and the Ionospheric Residual. In this paper, however, the noise of these combinations is investigated and compared, illustrating the expected measurement precisions from the different types of satellites, and their comparisons.